2019
DOI: 10.1177/1049732318825145
|View full text |Cite
|
Sign up to set email alerts
|

Plunging Into a Dark Sea of Emotions: Professionals’ Emotional Experiences Addressing Child Abuse in Interviews With Children

Abstract: Comprehending professionals’ emotional challenges when addressing child abuse can help to improve identification, protection, and care for exposed children. This study presents an interpretive description analysis of qualitative interviews with ten child protective services workers and nine child mental health services psychologists in Norway. The participants described intense negative reactions due to addressing child abuse during assessments and investigations. We identified five main themes: (a) facing chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…As evident from the sub-synthesis, health professionals also experienced unexpected rewards from their work, and they found sharing these aspects of the work with colleagues beneficial as well. Moreover, training and structures that can reduce their feelings of inadequacy and fear of making things worse for the child (Albæk et al, 2020 , 2018 ) are likely important measures to support health professionals in addressing CSA in ways that are helpful for the survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As evident from the sub-synthesis, health professionals also experienced unexpected rewards from their work, and they found sharing these aspects of the work with colleagues beneficial as well. Moreover, training and structures that can reduce their feelings of inadequacy and fear of making things worse for the child (Albæk et al, 2020 , 2018 ) are likely important measures to support health professionals in addressing CSA in ways that are helpful for the survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Some research exploring professionals’ experiences of addressing child adversity more generally has pointed to the emotional burden of facing children’s suffering and the cruelty in what they have been subjected to. Health professionals reported feelings of inadequacy and fear of making things worse for the child when doing this work and felt they were being mean to the child when asking about adversity (Albæk et al, 2020 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notice that some of the 7 types depict feelings that draw the researcher closer to the participant (e.g., feeling with) whereas other types indicate distancing (the feeling of being used). One of the emotional challenges for interviewers of abused children (Albaek et al., 2020) was this struggle to achieve a balance between empathy and self‐protection; when interviewers tried to protect themselves by maintaining some distance, they felt guilty. My trainees have profited from reading a classic paper by Cowles (1988), who interviewed survivors of murder victims.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of trust also extended to undermine their belief in the criminal justice system (Massey et al, 2019;Nixon, 2019), which led to emotional distress, such as feelings of hopelessness or powerless in their roles and feeling guilty when not able to help or support clients to the extent they would wish to (Albaek et al, 2020;Brend et al, 2020;Nixon, 2019). The hierarchical structure of the criminal justice system, or the mental health system in some cases (Albaek et al, 2020), meant that professionals found it difficult to do their job. They often faced ethical and professional dilemmas about their role and the usefulness or necessity of their role (Backe, 2018;Javaid, 2017).…”
Section: Effects Of Working With Victim-survivors Of Sexual Violence On Professionals' Well-beingmentioning
confidence: 99%
“…They often faced ethical and professional dilemmas about their role and the usefulness or necessity of their role (Backe, 2018;Javaid, 2017). Faced with these issues, staff felt stressed and unable to cope with the demands of the job, their sense of selfworth, confidence, and self-efficacy as professionals were diminished, felt disempowered and meaningless in their job, as well as experiencing constant doubt and ruminations over decisions taken due to no longer perceiving themselves as skilled to a high standard (Albaek et al, 2020;Brend et al, 2020;Gatuguta et al, 2019;O'Dwyer et al, 2019). This effect was exacerbated when they lacked clear guidance, guidelines, or resources (Backe, 2018;Kreinath, 2019), when there was an overreliance on procedures, and when they did not feel that the organizations they worked for would support their decisions (Albaek et al, 2020).…”
Section: Effects Of Working With Victim-survivors Of Sexual Violence On Professionals' Well-beingmentioning
confidence: 99%